Perancangan Alat Sortir Buah Durian Berdasarkan Kandungan Gas Dan Berat Dengan Arduino Uno - Ali, Edi; Jasmir; Riyadi, Willy (LPPM Universitas Dinamika Bangsa, 2024)
Indonesia, as an agrarian country with the majority of its population engaged in farming, holds significant potential in durian fruit production, ranking as the third-largest commodity worldwide. Despite high domestic demand for durian, imports remain significant. To enhance production self-sufficiency, this research develops a durian fruit sorting system based on MQ-9 and Load Cell sensors using the Arduino Uno microcontroller. The testing results indicate that the durian fruit sorting system, utilizing MQ-9 and Load Cell sensors with the Arduino Uno microcontroller, has been effectively implemented. Load cell testing demonstrates satisfactory performance in measuring durian weight with an acceptable level of error. The MQ-9 sensor successfully measures ADC values and assesses durian ripeness with adequate accuracy. Servo module testing with PCA9685 shows a good response to Arduino commands. Overall, this system can operate well in the durian fruit sorting process based on weight and ripeness, providing an automated solution to enhance efficiency and accuracy in durian production in Indonesia.